Time in a bottle: Use of soil archives for understanding long‐term soil change. Issue 3 (16th February 2022) - Bergh, Emma L.; Calderon, Francisco J.; Clemensen, Andrea K.; Durso, Lisa; Eberly, Jed O.; Halvorson, Jonathan J.; Jin, Virginia L.; Margenot, Andrew J.; Stewart, Catherine E.; Pelt, Scott Van; Liebig, Mark A.
Abstract: Soil archives preserve a snapshot of soils from a specific time and location, allowing researchers to re‐evaluate soils of the past in the context of the present for an improved understanding of long‐term soil change. To date, the extent of soil archive use in the peer‐reviewed literature is poorly inventoried. Here, we document the characteristics and distribution of global soil archive use, as found in 245 publications, following an exhaustive search of English language journals. Soil archive use has increased substantially since 1980, reaching 59 publications between 2016 and 2020. The age of soil archives across the compilation ranged from 5 to 160 yr, with mean and median archive ages of 48 and 37 yr, respectively. Publications using soil archives originated mostly from countries in the northern hemisphere, with the top five reporting countries including the United States (61), United Kingdom (52), New Zealand (21), Canada (18), and China (14). Land uses associated with soil archive publications were dominated by agroecosystems, specifically land planted to annual crops. Forty‐seven percent of investigations focused on changes in soil C, N, or organic matter, whereas investigations of other subjects did not exceed 20% each. The compilation is publicly available online. As demands on soils increase, archives will serve as an invaluable tool for understanding long‐term soil change in the Anthropocene era. Multiregional coordination and increased investment in curation and retention of soil archives are recommended to preserve these irreplaceable resources. Core Ideas: Archived soil samples facilitate an improved understanding of long‐term soil change. A literature review was conducted to compile metadata documenting soil archive use. Since 1980, there has been an accelerating use of soil archives in research. Research is primarily focused on soil organic matter change in agroecosystems. Resources are needed to support soil archives, especially in developing countries.